Changing seroprevalence to SARS-CoV-2 in health care workers during COVID-19 pandemic - VK Sashindran; Abdul Raheem Sheikh; Sunita D Patil (Journal of Vaccines and Immunology - Peertechz Publications, 2022)
Background and objective: The entire world is reeling under the COVID-19 pandemic caused by coronavirus SARS-COV-2. A longitudinal study was planned to understand the evolving pattern of seroprevalence of anti-SARS CoV-2 antibodies in a cohort of health care workers. Method: A prospective study was conducted among the health care workers categorized as doctors, nursing staff, paramedical staff, and housekeeping staff. A qualitative estimation of total antibodies (IgM+IgG+IgA) against SARS-CoV-2 was carried out using an ELISA kit in July and November 2020.  Results: Total 443 blood samples were collected on July 20 and 214 samples in November. A cohort of 140 health care workers was selected from July to November 2020 data. The overall seroprevalence in HCWs was 8.35% in July 2020 and it increased to 26.63% in November 2020. The overall seroprevalence in the HCW cohort also revealed an increase from 12.14%. 30.71%. In the cohort of healthcare workers, there was a constant seroprevalence in nursing staff (10.5%) and housekeeping staff (25%) while a statistically significant (p0.002) rise in seroprevalence rate (12.6 to 41.37) was noted in the paramedics. Conclusion: The seroprevalence of anti- SARS-CoV2 antibodies in asymptomatic HCWs increased from 8.35% to 26.63% over a period of 4 months. A significant rise in seroprevalence was noted amongst nurses (p0.0005) and paramedics (p0.007). The seroprevalence data of the cohort group revealed a statistically significant rise in seroprevalence in paramedics (p 0.002) as compared to other categories of healthcare personnel.